Cognitive behaviours and connectivity mental system in second language context: declines in sensitive period? - Figueiredo, Sandra (2018)
Regarding the lack subsisting in the second language acquisition research, related with the cognitive processing, it was developed a screening instrument to observe the linguistic behaviour on the several levels. Findings in what concerns the decoding competence will be discussed, regarding the performance of monolinguals and second language learners (130 individuals) in tasks such as the dichotic hearing test. Will be suggested a mental linguistic system of connectivity that could fossilize even in the younger learners. The concept of phonological awareness is not necessarily involving the consciousness level, influencing judgement behaviours in the linguistic task and compromising the phonological representations.